Pelatihan E-Module Materi Ekonomi Menggunakan Flip Pdf Profesional untuk Kemandirian Belajar Ekonomi dalam Pembelajaran Daring Selama Pandemi Covid-19 - Wardani Purnama Sari; Salmiah; Mahdar Ernita; Naskah; Rohani; Ifdilah Risqa (Tasnim Journal for Community Service, 2022)
Many economics learning activities are still teacher centered learning. Therefore, in order to streamline the teaching and learning process and increase student independence in learning, it is necessary to develop teaching materials with self-instructional characteristics to support a student's independent learning activities, especially in economics subjects. E-module is a learning tool or tool that contains material, methods, limitations and ways of evaluating that are designed in a systematic and attractive way to achieve the expected competencies in accordance with the level of complexity electronically. This service activity was carried out for 2 days by providing training related to the process of making E-Modules from the initial stage to finishing. The target group for community service activities for Prospective Economics teachers is Economics Education Students at the Faculty of Economics and Business, UIN Suska Riau, while the service method is carried out using lectures, demonstrations and exercises. overall E-Module development assistance activities Using Professional Pdf Flips to equip economics education students as future teachers in relation to E-Module development, because seeing the current learning situation during the covid 19 era all learning is done online / online like it or not the teacher must be ready in the current learning process, with the development of E-modules this is one of the best ways in the learning process especially in Economics material.